TIPU MUSLIHAT SEBAGAI UNSUR PEMBERATAN PIDANA DALAM KASUS TINDAK PIDANA PENCUCIAN UANG (STUDI KASUS PUTUSAN NOMOR 2007 K/PID.SUS/2021) - Cresentius Raymond Felix Benedict Santoso (Constitutum: Jurnal Ilmiah Hukum, 2024)
Money laundering is a process carried out by someone to obscure money from illegal criminal acts so that it appears legitimate and clean so that the perpetrator can hide its origin from the government and related authorities. If the process also involves other illegal activities besides money laundering, the perpetrator can be threatened with a heavier penalty, which can aggravate the main crime. This study discusses the application of heavier criminal qualifications in money laundering cases and the judge's considerations in the Supreme Court Decision Number 2007K/PID.SUS/2021. The research method used in this study is normative juridical. The results of the study show that the heavier penalty in money laundering cases is aggravating penalties with certain elements that can aggravate the main crime. However, Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering only regulates aggravating penalties for corporations, so for individuals, the Criminal Code is used as the basis. The judge's consideration to cancel the High Court's decision which acquitted the defendant from all charges and retried the defendant was correct. This is because the defendant has hidden the proceeds of his crime, so he can be charged with money laundering. Aggravating considerations canalso be justified because the defendant used fraudulent means to obtain the money. However, the defendant was given a reduced sentence because of his contribution to the company that was harmed, so his sentence was reduced to only 3 years.